Active Buffer Matrix in Nanoparticle‐Based Silicon‐Rich Silicon Nitride Anodes Enables High Stability and Fast Charging of Lithium‐Ion Batteries. Issue 26 (19th August 2022) - Kilian, Stefan O.; Wankmiller, Björn; Sybrecht, Anna Margarete; Twellmann, Jonas; Hansen, Michael Ryan; Wiggers, Hartmut
Abstract: A very promising way to improve the stability of silicon in lithium‐ion battery (LIB) anodes is the use of nanostructured silicon‐rich silicon nitride (SiN x ), known as a conversion‐type anode material. To investigate the conversion mechanism in this material in detail, SiN0.5 nanoparticles are synthesized and examined as LIB anodes using a combination of ex situ X‐ray photoelectron spectroscopy and solid‐state 7 Li MAS NMR measurements. During the initial cycle, the conversion of SiN0.5 nanoparticles results in the formation of lithium silicides and a buffer matrix consisting of different lithium nitridosilicates and lithium nitride. These phases can be reversibly lithiated and contribute to the total reversible capacity of the silicon nitride active material. The structure of the material after conversion is best described by an amorphous solid solution. Further, it is shown that silicon‐rich silicon nitrides possess improved rate capability because of the higher ionic conductivity of the buffer matrix compared to pure silicon, and very fine dispersion of silicon clusters throughout the buffer matrix. Thus, unlike most conversion materials, the silicon‐rich silicon nitride exhibits an additional intrinsic active functionality of the buffer matrix that goes far beyond the mere reduction of electrolyte contact area and volume expansion. Abstract : SiN0.5 nanoparticles undergo a conversion reaction during initial lithiation, resulting in finely dispersed Si inside a buffer matrix consisting of Li2 SiN2 . Unlike other conversion materials, this buffer matrix shows electrochemical activity and reversible conversion to Li3 N and is a key factor for improved stability and fast charge through its highly dynamic Li buffering behavior and unique electrochemical properties.